Impact of early diagnosis and control of chronic respiratory diseases on active and healthy ageing. Issue 5 (7th March 2013) - Bousquet, J.; Tanasescu, C.C.; Camuzat, T.; Anto, J.M.; Blasi, F.; Neou, A.; Palkonen, S.; Papadopoulos, N.G.; Antunes, J.P.; Samolinski, B.; Yiallouros, P.; Zuberbier, T.
Abstract A debate at the European Union Parliament was held on 13 November 2012 on the Impact of early diagnosis and control of chronic respiratory diseases on Active and Healthy Ageing (AHA). The debate was held under the auspices of theCyprus Presidency of the European Union (2012) and represents a follow‐up of the priorities of the Polish Presidency of the European Union (2011). It highlighted the importance of early life events on the occurrence of chronic respiratory diseases later in life and their impact on active and healthy ageing. Epidemiologic evidence was followed by actions that should be taken to prevent and manage chronic respiratory diseases in children. The debate ended by practical, feasible and achievable projects, demonstrating the strength of the political action in the field. Three projects will be initiated from this debate: The first will be a meeting sponsored by the Région Languedoc‐Roussillon on the developmental origins of chronic diseases and ageing: from research to policies and value creation. The second project is being led by the WHO Collaborating Centre for Asthma and Rhinitis: Prevention of Asthma, Prevention of Allergy (PAPA). The third project is the GA2LEN sentinel network.